Implementation Challenges of Indonesia’s Electronic-Based Government System: An Edwards III Perspective - Habsana, Triska Yuninda Putri; Kencono, Dewi Sekar; Fridayani, Helen Dian (Jurnal Pemerintahan dan Kebijakan (JPK), 2026)
This study aims to analyze the implementation and challenges of the Electronic-Based Government System (SPBE) in Indonesia using George C. Edwards III’s policy implementation model, which encompasses four key variables: communication, resources, disposition, and bureaucratic structure. A descriptive qualitative method was applied, using secondary data from scientific journals, national SPBE evaluation reports, and official policy documents issued by the Ministry of Administrative and Bureaucratic Reform (PANRB). The findings revealed that SPBE implementation remains suboptimal, as indicated by inconsistent inter-agency coordination, gaps in human resource competencies and ICT infrastructure, resistance to shifts in work culture, and a fragmented bureaucratic structure that hinders system interoperability. Nevertheless, SPBE policy has contributed to initial improvements in transparency and efficiency of public service delivery in several regions. The novelty of this study lies in its use of Edwards III’s model to examine the disparity between national policy design and actual implementation at the regional level in the context of public-sector digital transformation. The results are expected to serve as a reference for formulating strategic efforts to strengthen digital governance through capacity building, system integration, and accelerated bureaucratic reform, aiming to achieve an adaptive, effective, and sustainable SPBE ecosystem.